Factors That Determine the Quality of Financial Statements in Islamic Financial Institutions - Raju, Amaliah Fahrani; Muhammad, Rifqi (Pinisi Business Administration Review, 2022)
Financial statements are the final result of the accounting process and financial statements are said to be of good quality if they meet the quality requirements of financial reports. Information on the factors that affect the quality of financial reports at Islamic financial institutions is still not consistent between one study and another. This study aims to analyze several factors that affect the quality of financial reports at Islamic financial institutions in Indonesia. The data used in this study is primary data in the form of a late questionnaire distributed to 130 respondents who were selected using the purposive sampling method. This research uses an SPSS analysis tool. The results of this study indicate that Sharia Auditing, Islamic Work Ethic, Utilization of Information Technology were found to have a positive effect on the Quality of Islamic Financial Reports while the Internal Control System (SPI) in this study was found to have no effect on the Quality of Islamic Financial Reports